TRACING THE TRAJECTORY OF FINANCIAL INCLUSION RESEARCH: A BIBLIOMETRIC ANALYSIS OF SCHOLARLY CONTRIBUTIONS (2004–2023) - Idicula, Ebby Joseph; Xavier, Manoj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study offers a comprehensive bibliometric analysis of the scholarly landscape on financial inclusion from 2004 to 2023, based on data extracted from the Web of Science (WoS) core collection through Clarivate Analytics. A total of 595 bibliographic records were examined, encompassing titles, abstracts, author keywords, and Keyword Plus categories. The analysis uncovers notable developments in research trends, thematic priorities, and collaboration patterns in the field. Contributions from 1,248 authors were identified, with collaborative research emerging as a dominant trend—only 90 authors were single contributors. This study provides meaningful insights into the intellectual structure, growth trajectory, and evolving discourse of financial inclusion research over the past two decades.